1979
DOI: 10.1111/j.1445-2197.1979.tb06443.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcaemia in Paget's Disease of Bone

Abstract: Albright in 1944 described a syndrome of hypercalcaemia in patients immobilized following fractures through bones affected with Paget's disease. This paper reports a further two cases in which this syndrome was con-. sidered the cause of hypercalcaemia with fatal outcome. Both patients had parathyroid adenomata. The literature is reviewed, and it is argued that no firm evidence for the existence of this syndrome has ever been put forward. The finding of hypercalcaemia in Paget's disease of bone should prompt a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…They are also effective for the treatment of hypercalcemia that can develop when some patients with Paget disease become immobilized. [98][99][100] Oral alendronate was shown to restore normocalcemia more rapidly than prednisolone in a series of pediatric patients with hypercalcemia due to vitamin D intoxication, with no effect on linear growth after treatment. 101 In adults with vitamin D intoxication and severe hypercalcemia, intravenous bisphosphonates are effective and were found superior to glucocorticoids in a small number of patients.…”
Section: General Measuresmentioning
confidence: 98%
See 1 more Smart Citation
“…They are also effective for the treatment of hypercalcemia that can develop when some patients with Paget disease become immobilized. [98][99][100] Oral alendronate was shown to restore normocalcemia more rapidly than prednisolone in a series of pediatric patients with hypercalcemia due to vitamin D intoxication, with no effect on linear growth after treatment. 101 In adults with vitamin D intoxication and severe hypercalcemia, intravenous bisphosphonates are effective and were found superior to glucocorticoids in a small number of patients.…”
Section: General Measuresmentioning
confidence: 98%
“…They are also effective for the treatment of hypercalcemia that can develop when some patients with Paget disease become immobilized. 98100…”
Section: Treatment Of Severe Hypercalcemiamentioning
confidence: 99%
“…This probably follows the early findings of normal circulating concentrations of PTH and calcitonin in PDB (49,50) that led most investigators to conclude that hormonal factors had no role in the expression of the abnormal bone remodeling process. A number of 73 patients with the combination of PDB and primary HPT is estimated to have been reported in the literature (2–31) . This makes possible to speculate of an uncommon association between two relatively high incident clinical entities.…”
Section: Co‐existing Pdb and Primary Hptmentioning
confidence: 99%
“…S ince the first description of the co‐existence of Paget's disease of bone (PDB) and hyperparathyroidism (HPT) by Albright and Reifenstein, (1) the majority of reports appeared in the medical literature regarding the association of the two disorders have been largely limited to case reports (2–30) . The only available study that extensively analyzed the topic was published in 1999 by Gutteridge et al (31) Therefore, even if the overproduction of PTH is reported in 12–18% of PDB, (32,33) detailed studies in such patients are limited, and the differential clinical diagnosis between the more frequently PDB‐associated secondary HPT and the rarely PDB‐associated primary HPT can represent a difficult task for physicians lacking a training in bone and mineral metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…However hyperparathyroidism must be excluded for concomitant parathyroid adenomas and hypercalcaemia have been described in an immobilized patient with Paget's disease (Gillespie, 1979).…”
Section: Case Reportmentioning
confidence: 99%